Analysis of meaning equivalence between dubbing and subtitles in “Lost Bullet” movie - Syamsul, Dina; Amalia, Farida; Sopiawati, Iis (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
The ideal translation is expected to meet five criteria of equivalence levels, which include equivalence at the word level, above the word level, grammatical level, textual level, and pragmatic level. This study examines the differences between dubbed and subtitled translations of the film Lost Bullet (2021) by Guillaume Pierret, focusing on the achievement of meaning equivalence according to Mona Baker’s theory (2018). Employing a qualitative descriptive method with note-taking techniques, the research analyzes five levels of equivalence. The findings indicate that subtitle translations more frequently meet these equivalence levels compared to dubbing. Grammatical equivalence is the most commonly achieved level in both dubbing and subtitles, while pragmatic equivalence is the least fulfilled in subtitles, and above the word level equivalence is least achieved in dubbing. Additionally, the study uncovers notable differences in translating idiomatic expressions, slang, and technical terms. Dubbing tends to prioritize the use of more expressive language, along with adjustments in intonation to create a livelier atmosphere. In contrast, subtitles emphasize brevity and conciseness to facilitate the viewers’ visual understanding without compromising the essence of the conveyed message. In contrast, subtitles emphasize brevity and textual conciseness to facilitate viewers’ understanding without compromising the core message. Thus, the findings of this study are expected to contribute to the understanding of translation quality while considering the achievement of meaning equivalence in both dubbing and subtitle translations, as well as enriching cross-language communication through film media.